2021
DOI: 10.3389/fimmu.2021.679770
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Increase After rh-MOG Stimulation in Non-Relapsing but Decrease in Relapsing MOG Antibody-Associated Disease at Onset in Children

Abstract: BackgroundMyelin oligodendrocytes glycoprotein (MOG) antibody-associated disease (MOGAD) represent 25% of pediatric acquired demyelinating syndrome (ADS); 40% of them may relapse, mimicking multiple sclerosis (MS), a recurrent and neurodegenerative ADS, which is MOG-Abs negative.AimsTo identify MOG antigenic immunological response differences between MOGAD, MS and control patients, and between relapsing versus non-relapsing subgroups of MOGAD.MethodsThree groups of patients were selected: MOGAD (n=12 among whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…This general distribution of MOGAD phenotypes was also observed when assessing all identified studies (Table 1). Overall, 39 identified articles (including the six aforementioned incident cohort studies) reported the phenotype at initial presentation for 1,686 pediatric MOGAD patients 4–6,8,11–45 . Most of these studies were limited by the potential for selection bias in patient identification (e.g., patients with stored serum available for retrospective MOG‐Ab testing, relapsing disease course, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…This general distribution of MOGAD phenotypes was also observed when assessing all identified studies (Table 1). Overall, 39 identified articles (including the six aforementioned incident cohort studies) reported the phenotype at initial presentation for 1,686 pediatric MOGAD patients 4–6,8,11–45 . Most of these studies were limited by the potential for selection bias in patient identification (e.g., patients with stored serum available for retrospective MOG‐Ab testing, relapsing disease course, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…In patients with MOGNR at onset of the disease, we recently found a higher Th17 response to rh-MOG than in patients with MOGR. 12 Th17 has been associated with demyelinating diseases in children and adults during inflammatory events, 42 , 43 in particular in children with MOGAD. 13 In addition, Th17-related cytokines G-CSF and IL-6 levels are increased in MOGAD, 13 and IL-6 levels in CSF correlate with MOG antibody levels in paediatric patients with monophasic acquired demyelination syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + Foxp3 + T regs were significantly increased in response to rh-MOG in MOGNR, while CD45RA − Foxp3 + T regs decreased upon rh-MOG stimulation in relapsing MOGAD (MOGR) patients. 12 It was suggested that MOG Abs and MOG-autoreactive lymphocytes might be involved in MOG Abs-associated demyelination 13 and axonal damage. 14 We therefore decided to evaluate axonal injuries using biological markers in MOGR and MOGNR.…”
Section: Introductionmentioning
confidence: 99%
“…Th17 responses are higher in MOGAD patients. Our lab used different MOG peptides for in vitro stimulation and showed MOGAD patients had more IL17+ and IL17+IFNγ+ (double positive) central memory cells than healthy controls (123). When relapse and remission MOGAD samples were compared, there was an increased proportion of IL17+, IFNγ+, and IL17+IFNγ+ CMCs after stimulation with several individual MOG peptides in MOGAD patients at the time of relapse (123) (72,113,125).…”
Section: T Cellsmentioning
confidence: 97%
“…Recently, a multinational study showed that IL6 receptor blockade with tocilizumab is therapeutically effective and safe in MOGAD and NMOSD (146). Increased TNFα, on the other hand, could also affect BBB permeability through We recently reported that A20, a negative regulator of the NF-κB pathway, is decreased in the serum during relapses on an individual level (123). Interestingly, steroids increase A20 expression in CD4 T cells.…”
Section: Biomarkers and Therapeutic Mechanismsmentioning
confidence: 99%